THE ROLE OF ISLAMIC ENDOWMENTS (WAQF) IN MITIGATING ECONOMIC INEQUALITY: EVIDENCE FROM THE INDONESIAN CONTEXT - Muhammad Putra Aprullah; Wida Fadhlia; Cut Afrianandra; Rulfah M. Daud (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the potential of waqf as a strategic mechanism for addressing economic inequality in Indonesia through a Systematic Literature Review (SLR) approach. This study examines relevant academic literature and institutional reports from various sources, including BAZNAS, LAZIS, Bank Indonesia, OJK, and other related institutions, using a methodological approach based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The literature selection process was conducted systematically to identify, screen, and evaluate studies that discuss the relationship between waqf—particularly cash waqf—and the reduction of economic inequality in the Indonesian context. The analysis was conducted using a theoretical framework of income distribution and governance. The results of the study indicate that waqf, particularly in the form of productively managed cash waqf, has significant potential to support wealth redistribution, economic empowerment of vulnerable communities, and strengthen the Islamic social finance ecosystem in Indonesia. However, challenges in governance, waqf literacy, and synergy between institutions remain significant obstacles to realizing this potential. This study recommends strengthening waqf governance, integrating waqf and formal financial institutions, and increasing the capacity of communities to participate as waqif (donors) actively.